Assessment of the Arthroscopic Double-Row Restoration Technique’s Reliability and Operational Results for Shoulder Cuff Reconstruction - Qaisar Alam, Yasir Mahmood, Jawad Khan, Nek Muhammad Khan, Tahir Mehmood Khattak, Mohib Ullah Khan, Khurram Shahzad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims at evaluating the effectiveness of shoulder cuff restoration by arthroscopic surgery in dual row repair mode and shows 30 months of practical results, an ASES-based scoring system was developed. Methods: This study was conduced at mayo hospital Lahore in orthopedics department and the duration of this study was from October 2021 to march 2023. 23 patients who had significant rotator cuff tears repaired arthroscopically in a double-row fashion are included in this cross-sectional research. The operating surgeon performed a clinical assessment on patients who had been admitted for surgery in the outpatient setting both before and after surgery, as well as during follow-up visits at six weeks, three months, six months, and one year. The last examination took place on average 30 months after surgery. Using a scoring system based on a modified ASES score, the function of the patient was evaluated both preoperatively and postoperatively, and the results were compared. Based on the Modified American Shoulder and Elbow Society (ASES) score, a patient-rated questionnaire was utilized to assess shoulder and elbow function. Three parts make up the questionnaire, the first of which included questions regarding pain and had six components with a total weight of 30 points. The existence of pain, its location, and if the patients had discomfort at night were all questions that were posed to the patients. A visual analog pain scale from 0 to 10 was used to assess the degree of the patient’s pain as well as their usage of drugs. The second phase, which included 10 components and a weighted average of 50 points, examined candidates’ capacity to carry out everyday tasks. On a scale of 0 to 5, patients were asked to assess their level of competence to accomplish tasks while accounting for any challenges they may have encountered. The shoulder instability was evaluated in the last portion using a visual analog scale with a range of 0 to 10. Patients were divided into four groups based on the grading system: Excellent result (score >75), Good outcome (score 50-75), Fair outcome (score 25-50), and Poor outcome (score < 25) Results: At the time of the last follow-up, there was a substantial improvement in the mean operational result scores depending on the Patient Self-Assessed Questionnaire (p-value < 0.01). By using magnetic resonance imaging to evaluate repair integrity 12 months after surgery, it was discovered that 16 patients had type-I repairs, 2 patients had type-II repairs, and only 1 patient had type-III repairs. For enormous tears, the study’s retear rate was 5%. Comparing the type-III repaired shoulders to the other kinds of repaired shoulders, the type-III repaired shoulders showed substantially worse functional outcomes in terms of total scores and strength (p-value < 0.01). Practical Implication: In the practical implication of this study we discovered that the arthroscopic double-row restoration approach is a successful treatment for repairing large rotator cuff injuries with a low chance of re-tear and a big increase in activity levels. Conclusions: In this research, we discovered that the arthroscopic double-row restoration approach is a successful treatment for repairing large rotator cuff injuries with a low chance of re-tear and a big increase in activity levels. Keywords: double-row technique, restoration, shoulder cuff, arthroscopically, resonance imaging